Design of Wideband Circular Patch with Symmetric Strips Antenna for 5G Applications - Supada Srisukhot; Wutthipong Thanamalapong; Chuwong Phongcharoenpanich; Suthasinee Lamultree (My University, 2021)
In this research, a circular patch antenna encircled by wide-circular-slot incorporated with symmetric strips is designed to operate over the middle-band of 5G applications. This proposed antenna is constructed of a copper and glazed on FR4 substrate with ε r of 4.3 and height of 1.6 mm. It is fed by a 50-ohms coplanar waveguide, which printed on a same side of the radiating circular patch. Obviously, it exhibits a bidirectional pattern with 10 dB return loss, minimum and maximum gains of 1.76 dBi, and 5.64 dBi, respectively covered 2-6 GHz. All appropriated parameters have been carried out by using an electromagnetic simulation tool. To evaluate its suitability in 5G applications, numerical results will be investigated and analyzed.
Keywords: Antenna Design and Analysis; Microwave Engineering and Waveguides; Advanced MIMO Systems Optimization